(untitled) (Research, Society and Development, 2020)
The sugar and alcohol sector in Brazil has undeniable advantages when compared with other global competitors in the production of sugarcane by-products. Thus, the objective of this work was to identify the significant factors at the price of the shares of three organizations in the Brazilian sugar-energy sector: Biosev (BSEV3), São Martinho (SMTO3), and Cosan (CSAN3). Specifically, it was verified how these factors influence or are associated with the price of such shares, to understand their trend movement, and, with this, increase the investment decision power in these companies at opportune times. It is descriptive research with a quantitative approach and an interdisciplinary character, addressing statistical, accounting, and economic-financial analysis. Data concerning 15 variables were collected from secondary sources, between January 2015 and March 2020. The results showed that companies have different variations in share prices. The Biosev and São Martinho groups have similar market trends, and the Cosan group maintains the opposite trend to the others. It was concluded that the sugar-energy sector is a good investment option, because had a significant financial evolution with the appreciation of stock prices in recent years, in particular, due to the increase in prices of VHP sugar and hydrated ethanol.